2023
DOI: 10.5455/njppp.2023.13.01052202304022023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, and practices toward pharmacovigilance among under graduate medical students of a tertiary care teaching hospital of central India

Abstract: Background: Pharmacovigilance is the science and activities relating to the detection, assessment, understanding, and prevention of adverse effects or any other possible drug-related problems. Adverse drug reaction (ADR) is global problem. It affects majority of population causing morbidity and mortality. Aims and Objectives: The present study was conducted to evaluate undergraduate student’s knowledge, attitudes, and practices (KAP) about pharmacovigilance and ADR reporting. Materials and Methods: KAP-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Our findings complies with the findings of Rermerman et al 25 In contrast to these finding, Tiwari et al from central India reported that the three fourth of the medical students were aware about the PV and ADR reporting because their institute has functioning adverse drug reaction monitoring center where adverse events from all the clinical disciplines were being reported regularly as well as PV and ADR reporting were in the curriculum of the medical students so they were sensitized about the importance of the ADR reporting and patient medication safety. 26 However, in developing countries like Nepal the PV program is still in the initial stage and this could lead to poor knowledge score. Majority of the students are unaware of ADR reporting system in Nepal and the significance of PV.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings complies with the findings of Rermerman et al 25 In contrast to these finding, Tiwari et al from central India reported that the three fourth of the medical students were aware about the PV and ADR reporting because their institute has functioning adverse drug reaction monitoring center where adverse events from all the clinical disciplines were being reported regularly as well as PV and ADR reporting were in the curriculum of the medical students so they were sensitized about the importance of the ADR reporting and patient medication safety. 26 However, in developing countries like Nepal the PV program is still in the initial stage and this could lead to poor knowledge score. Majority of the students are unaware of ADR reporting system in Nepal and the significance of PV.…”
Section: Discussionmentioning
confidence: 99%